Update on Acrylic Resins Used in Dentistry - Raszewski, Zbigniew; Nowakowska-Toporowska, Agnieszka; Nowakowska, Danuta; Więckiewicz, Włodzimierz (Mini Reviews in Medicinal Chemistry, 2021)
Acrylic resins are the most commonly used materials in prosthetics and orthodontics until now. They have a well-documented history of use as biomaterials in the manufacturing of different types of dental appliances. The objective of this study was to describe the properties of acrylic resins and the processing methods used for these materials in dentistry. The review depicts the most important achievements in this area, indicating that the resin technology evolved in different directions. The mechanical and biological properties of acrylic resins were improved by the addition of mineral or natural fibers, and/or fillers, including nanofillers, as well as by poly(methyl methacrylate) surface modification. The presence of residual monomer was reduced as a result of postpolymerization activity. New types of acrylic resins were developed for processing Computer-Aided Design/Computer- Aided Manufacturing systems and three-dimensional printing.
Keywords: Acrylic resin